Laminated Cross‐Linked Nanocellulose/Graphene Oxide Electrolyte for Flexible Rechargeable Zinc–Air Batteries. Issue 14 (17th May 2016) - Zhang, Jing; Fu, Jing; Song, Xueping; Jiang, Gaopeng; Zarrin, Hadis; Xu, Pan; Li, Kecheng; Yu, Aiping; Chen, Zhongwei
Abstract : A solid‐state hydroxide‐conducting electrolyte with laminated structure based on functionalized graphene oxide and nanocellulose is demonstrated on a flexible, rechargeable zinc–air battery. Superior ionic conductivity, high water content, low anisotropic swelling degree, and excellent structural stability approve its promising application in advanced flexible, portable electrochemical energy conversion, and storage systems.